2016
DOI: 10.1111/jocn.13364
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian and bisexual women's sexual healthcare experiences

Abstract: This study's findings can be used to guide further research to identify ways to optimise clinicians' engagement with lesbian and bisexual women. Recognition of diversity and skilful communication are essential to rectify inequities and effectively target health information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 47 publications
1
35
0
5
Order By: Relevance
“…Muson and Cook (2016) convey the challenges of lesbian and bisexual women having to "come out" repeatedly to medical providers as a result of their clinicians' assumptions of heterosexuality. Lesbian and bisexual women report that a fear of being judged unfairly, based on assumptions of heterosexuality, create discomfort to further discuss medical concerns (Munson & Cook, 2016). The lack of attention to the sexual health of an LGBTQIA+ person contributes to decreased attendance to medical appointments and the decreased congruence of relationship between provider and client.…”
Section: Introductionmentioning
confidence: 99%
“…Muson and Cook (2016) convey the challenges of lesbian and bisexual women having to "come out" repeatedly to medical providers as a result of their clinicians' assumptions of heterosexuality. Lesbian and bisexual women report that a fear of being judged unfairly, based on assumptions of heterosexuality, create discomfort to further discuss medical concerns (Munson & Cook, 2016). The lack of attention to the sexual health of an LGBTQIA+ person contributes to decreased attendance to medical appointments and the decreased congruence of relationship between provider and client.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that using inclusive terms when talking about spouses is more likely to help sexual minorities disclose their sexual orientation (Law et al, ; Legere & MacDonnell, ). Women had also been given patient education and asked questions from a heteronormative viewpoint, as has been shown in previous research (Agénor et al, ; Munson & Cook, ). Thus, heteronormativity might lead to situations when lesbian and bisexual women do not receive the health care or patient education they need because they are unsure if the given guidance includes them.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies have shown health care to be heteronormative. Sexual minorities have described that they are "not seen" in health care because of its heteronormativity (Hayman, Wilkes, Halcomb, & Jackson, 2013;Munson & Cook, 2016), which has led them to feel that they are not welcome in health care (Czaja et al, 2016;Smith, 2015). Many had received patient guidance based on heteronormative assumptions (Agénor et al, 2015;Munson & Cook, 2016), and this was confusing for patients because they did not What does this paper contribute to the wider global clinical community • Not recognising the diversity of sexual orientations causes offence for lesbian and bisexual women.…”
Section: Heteronormativitymentioning
confidence: 99%
“…First, providers may assume that women accessing sexual and reproductive health services, especially family planning-related services, identify as heterosexual or are in exclusively opposite-sex sexual and romantic relationships [710]. Across studies, women report this assumption of sexual orientation and behaviors to be problematic, in part because of the burden it places on women to disclose their orientation in a context that may not be perceived as safe (i.e., where they will not be discriminated against) [8,11]. Second, sexual minorities may believe that their care providers are not adequately prepared to provide them with accurate sexual health information.…”
Section: Introductionmentioning
confidence: 99%
“…Second, sexual minorities may believe that their care providers are not adequately prepared to provide them with accurate sexual health information. Some sexualminority women report instances where they disclosed their identity and/or sexual behaviors and were then advised that they did not need to consider important reproductive health services, such as STI screens [7,8,12]. Such negative interactions with healthcare providers in clinical settings serve as a deterrent to seeking care among sexual minorities [7,13,14].…”
Section: Introductionmentioning
confidence: 99%